2022
DOI: 10.1021/acs.chemmater.2c02955
|View full text |Cite
|
Sign up to set email alerts
|

Material Perspective on HgTe Nanocrystal-Based Short-Wave Infrared Focal Plane Arrays

Abstract: After the use of nanocrystals as light downconverters, infrared sensing appears to be one of the first market applications where they can be used while being both electrically and optically active. Over recent years, tremendous progress has been achieved, leading to an apparent rise in the technologicalreadiness level (TRL). So far, the efforts have been focused on PbS nanocrystals for operation in the near-infrared. Here, we focus on HgTe since its narrower band gap offers more flexibility to explore the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…It is also worth pointing out that we do not notice any contribution from oxygen even though the film was prepared under air condition. This observation is consistent with the recent report by Zhang et al that concluded with the weak propensity of HgTe NCs for oxidation . This lack of oxidation will leave the state close to the valence band free from oxide contribution, which is critical for photoemission microscopy.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It is also worth pointing out that we do not notice any contribution from oxygen even though the film was prepared under air condition. This observation is consistent with the recent report by Zhang et al that concluded with the weak propensity of HgTe NCs for oxidation . This lack of oxidation will leave the state close to the valence band free from oxide contribution, which is critical for photoemission microscopy.…”
Section: Resultssupporting
confidence: 93%
“…This observation is consistent with the recent report by Zhang et al that concluded with the weak propensity of HgTe NCs for oxidation. 12 This lack of oxidation will leave the state close to the valence band free from oxide contribution, which is critical for photoemission microscopy. X-ray beam focusing is accomplished by introducing a Fresnel zone plate over the synchrotron beam, which focuses the beam from a conventional level of 100 μm down to 700 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we observe no contribution coming from oxygen (O 1s state is expected to appear with a 532 eV binding energy) despite the preparation of the sample in air, which confirms the weak oxidation susceptibility of HgTe. 43…”
Section: Resultsmentioning
confidence: 99%
“…In the infrared, the prospect of bringing cost disruption to a spectral region where detectors and sources are dramatically more expensive than their counterparts operating in the visible range has also spurred interest in colloidal nanomaterials. Some clear successes have been obtained through the design and fabrication of components such as on-chip integrated sensors, , infrared cameras, spectrometers, and LEDs. , …”
Section: Introductionmentioning
confidence: 99%